PO-23 - Expression of heparanase in cancer as biomarker of malignancies: overexpression in an aggressive, poor survival gastric cancer "gastric signet ring cell carcinoma" compared with that of other gastric cancers. Issue 140 (April 2016) - Fourgeaud, C.; Derieux, S.; Mirshahi, S.; Besbes, S.; Chidiac, J.; Mahé, I.; Contant, G.; Pocard, M.; Soria, J.; Mirshahi, M.
Abstract : Introduction: Gastric signet ring cell carcinoma (GSRC) is a distinct entity among of other gastric cancer. With unknown etiopathology, their incidence is increasing and it presents a low sensitivity to chemotherapy. Aim: Here, we studied the expression of the heparanase (HPA) in cancer tissues from GSRC patients and several cancer cell lines. HPA is an endo-β-D-glucuronidase, capable of cleaving the lateral chains of heparan sulfate on cell surfaces and the extracellular matrix at acidic pH. Apart from its well-characterized enzyme activity, HPA also has independent enzymatic functions, such as up-regulation of vascular endothelial growth factor (VEGF) -A and VEGF-C and activation of intracellular signaling pathways involved in, survival, migration and proliferation of tumor cells. It can also induce an hypercoagulability by a non-enzymatic manner. Materials and Methods: HPA was tested in several cancer cell lines from ovaries (OVCAR-3, SKOV-3), breast (MDAMB231, MCF7) colon (LS-174), lung (A549), uterus (HELA) and gastric (adenocarcinoma (AGS) and GSRC (KATO-III) using several techniques such as RT-PCR, Q-PCR, immunocytochemistry, flow cytometry and degradation of Fondaparinux at pH 5, evaluated by its anti Xa activity evaluated by Factor Xa amidolytic activity. The amount of HPA mRNA in the biopsy simples of gastric adenocarcinoma (n = 10) and GSRC (n = 11) in tumors and their environment were analyzed. Results: HPA gene is expressed in all cancer cell lines, but its level varies depending on the tumor cell line. In biopsies of gastric cancer, the HPA gene is more expressed in the tumor regions (p = 0.0002) and tumor environment (p = 0.015) in GSRC than in gastric adenocarcinoma. B) The activity of HPA, evaluated by degradation of Fondaparinux at pH 5, 1) in the supernatants of 10 6 cancer cells: the residual activity of Fondaparinux after 2 hours incubation at 37°C with OVCAR-3 supernatant was of 70% of control value, and of 80% with KATO-III cell supernatants. 2) in patient's plasmas, this technique cannot be used because the site of degradation of fondaparinux by heparanase is masked by AT present in plasma. Conclusions: Heparanase was found in in many cancer cell lines and its level depends on origin of tumor cells and on its aggressivity. Taking into account the pro-metastatic functions, proangiogenic and procoagulant activity of HPA and its overexpression in gastric signet ring cell carcinoma of poor prognosis and its cell line, HPA can be considered as a biomarker of malignancy and as a therapeutic target in GSRC patients.